2019
DOI: 10.3390/nu11092116
|View full text |Cite
|
Sign up to set email alerts
|

What Is Known About the Nutritional Intake of Women during Pregnancy Following Bariatric Surgery? A Scoping Review

Abstract: Optimising the diet and weight of women prior to and during pregnancy is of paramount importance to both maternal and offspring health. In women who become pregnant after bariatric surgery, evidence suggests a better overall obstetric outcome in comparison to women with severe obesity managed conservatively. Historically, most studies in this population group have monitored supplement adherence or serum concentrations of micronutrients, rather than dietary intake. The aim of this study was to synthesise curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
0
10
0
4
Order By: Relevance
“…After sleeve gastrectomy, nutrition for patients begins with liquids and consists of very limited calories in the early postoperative period. This is the most catabolic period with significant weight loss [19]. Pregnancy closer to bariatric surgery may lead to more probable nutritional problems, which may occur with limited food and calorie intake.…”
Section: Discussionmentioning
confidence: 99%
“…After sleeve gastrectomy, nutrition for patients begins with liquids and consists of very limited calories in the early postoperative period. This is the most catabolic period with significant weight loss [19]. Pregnancy closer to bariatric surgery may lead to more probable nutritional problems, which may occur with limited food and calorie intake.…”
Section: Discussionmentioning
confidence: 99%
“…Micronutrients are essential for foetal development ( Table 4 ). There is no unanimous agreement on preventive supplementation during pregnancy, which will depend on the characteristics of the pregnant woman and the risk of deficiency in her environment [ 43 , 44 , 45 , 46 , 47 ].…”
Section: Micronutrients Pregnancy and Bariatric Surgerymentioning
confidence: 99%
“…There are few data on dietary intake in pregnant women with previous barbaric surgery. Available information suggests that it may be insufficient in essential nutrients [ 44 ]. In general, malabsorptive techniques are associated with a higher risk of complications in pregnancy after BS, especially maternal anaemia and low-birth-weight babies [ 45 ].…”
Section: Micronutrients Pregnancy and Bariatric Surgerymentioning
confidence: 99%
“…In several studies and case reports, evidence could be found that after bariatric surgery women who become pregnant suffer from micronutrient deficiencies, e.g., vitamins A, D, C, B1, and B9 and selenium [74][75][76][77][78]. Furthermore, a study submitted that intake of proteins and omega 3 fatty acids could be difficult [77]. In terms of vitamin K, which is important in the prevention of intracranial bleeding in babies, there was no significant difference between women who underwent Roux-en-Y gastric bypass and those who did not.…”
Section: Pregnancy and Breastfeedingmentioning
confidence: 99%